Simulation of the Hydrological Components of Dez River Basin by the classification of Land Use Categories Using SUFI-2 Algorithm - Elaheh Asgari; Mohammad Baaghideh; Majid Hosseini; Alireza Entezari; Asghar Kamyar (تحقیقات کاربردی علوم جغرافیایی)
Understanding the main components of the watershed water basin and analyzing their hydrologic behavior are among the key components of any planning and management procedures in the field of water resources engineering. Today, the need to use modern technologies in hydrological modeling of watersheds has been discussed more than before. The purpose of this study is the simulation of hydrological components in various land use categories in the catchment area of the Dez river basin. Since the tool used in the research is the SWAT model and the SUFI-2 algorithm, the database used include a range of input data. In order to determine the level of sensitivity of the model to the input parameters, global sensitivity analysis was performed. Then, by adjusting the selected parameters and using the observation current, the model was calibrated and validated for the periods 2007 - 1994 and 2013 - 2008, respectively. The coefficients of NS, R2, P-factor and R-factor confirmed the model's ability to simulate river flow in the studied basin. The results of the model showed that the areas with forest use share the highest contribution to aquifer nutrition, and the barren lands have the highest surface runoff. Surface runoff has the leading role in creating the main stream of the river and after that the main flow has been effective in this area. The forest use change to Agricultural lands and pasture will change the hydrological parameters of the basin, and the result of these changes will lead to the increase in the surface runoff, the reduction of nutrition of groundwater resources and the reduction of river basin water. The SWAT model can be used as a precursor model in watershed management studies.